Operational Calculus of Modified Subset Construction (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2023)
We present the continuation of studying Extended Regular Expression (ERE) on the view of modified subset construction within the overridden operators like intersection, subtraction, and re-written complement. As before we have stated that in this case the complexity has a decreasing nature and tendency. We will give the strict definition of the operational part of this modified subset construction which is due to Rabin and Scott. The complexity of algorithm remains a magnitude less than NP-hard problems for which we have given the strict proof of equivalence in the prior work, so this work continues the studying of the comparable proof for a variety of problems to be computationally complex, however, explainable in terms of unified approach like operational calculus. In this calculus the general points of research are given to the representation of modified subset construction with at least two operands which are to be computed by subset construction and in terms of complexity of the effective algorithm they are computed using modified subset construction.
Keywords: subset construction; extended regular expressions; modification; operations; calculus